Modelling the relationship between oversize fragments and nature of rock mass for a sublevel caving operation - Manzoor, Sohail; Gustafson, Anna; Schunnesson, Håkan (International Journal of Rock Mechanics and Mining Sciences, 2023)
Rock fragmentation is vital in a sublevel caving operation. The oversize fragments are the most undesiredfragmentation category because of their challenges; as such, they require special attention. This study carried outa field test in one of the LKAB’s iron ore mines in northern Sweden to analyse the occurrence of oversizefragments. The analysis involved correlation and regression tests and was performed for different types of rockmasses. The results showed that an increase in the percentage of solid rock mass caused an increase in thepercentage of oversize fragments. The other rock types, including slightly fractured, highly fractured, and rockmass with minor and major cavities, tended to have a reduced percentage of oversize fragments. The resultsindicate that oversize fragments can be predicted using linear regression or partial least square regression modelswith R2 values of 0.78 and 0.73, respectively. Validerad;2023;Nivå 2;2023-06-08 (joosat); Licens fulltext: CC BY License This article has previously appeared as a manuscript in a thesis.